Evolution of ZnO nanostructures as hexagonal disk: Implementation as photoanode material and efficiency enhancement in Al: ZnO based dye sensitized solar cells - Parra, Mohammad Ramzan; Pandey, Padmini; Siddiqui, Hafsa; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Haque, Fozia Z. (Applied Surface Science, 2019)
Hexagon shaped pristine and Al doped ZnO nanodisks (NDs) with exposed +/- [0001] polar facets were successfully synthesized using modified sol-gel method without the involvement of any structural directing or capping agents. It was investigated that OH- ions in mixed solvent system is responsible for pore formation and inhibit the growth of ZnO along the direction of c-axis leading to a high percentage exposure of active +/- [0001] polar facets and encourage the formation of ZnO NDs. Crystallographic analysis revealed that crystallite size and lattice constants are decreased, with the addition of Al3+ ions. The results obtained from Raman, and XPS analysis further corroborated with the XRD results, revealed the successful incorporation of Al3+ ions into ZnO lattice. Optical study revealed the band gap tunability with the incorporation of Al ion as dopant. Enhanced power conversion efficiency (PCE) of 1.96% (J(sc) similar to 7.69 +/- 0.23 mA/cm(2)) was observed for Al: ZnO hexagonal NDs based DSSC. The increased PCE in Al: ZnO based DSSC can be attributed to the higher inner surface area for dye anchoring by the interconnected network of the disk-like structure. The obtained results were satisfactory and most importantly the synthesis procedure proposed in present work is excellent for the synthesis of perfectly hexagonal shaped disks under precised synthesis parameters. The device interface study was further conducted using electrochemical impedance spectroscopy which revealed better charge transport process and charge storage ability with the incorporation of Al3+ ions into ZnO lattice.
Keywords: dye sensitized solar cells; Hexagonal disks; Sol-gel method; ZnO